Development of Syrup from Mulberry (Morus alba L.) and its Quality Evaluation under Ambient and Refrigerated Storage Conditions - Hamid; Thakur, N. S.; Kumar, Pradeep; Thakur, Abhimanyu (International Journal of Bio-resource and Stress Management, 2023)
Mulberry (Morus alba L.) is one of the underutilized fruit which is a rich source of antioxidants like phenols and anthocyanins besides its delicious taste and strong aroma. In India the mulberry fruit trees are generally grown for rearing silkworms and to a small extent for its fruits. Therefore, investigations were conducted to develop syrup in the Department of Food Science and Technology, Dr YSP UHF Nauni, Solan (HP) during the year 2015 and its quality evaluation during storage. Different combinations of juice (20, 25, 30 and 35%) and TSS (65 and 70 °B) were tried to standardize proper combination for syrup. The syrup prepared by following the best selected recipe was packed in glass and PET bottles and stored for six months under ambient (20–25 °C) and refrigerated temperature conditions (4–7 °C). Out of 8 different treatment combinations of juice and TSS tried, syrup prepared with 25% juice, 70 °B TSS and 1.60% acid was found to be best on the basis of sensory and some physico-chemical characteristics of the product. Syrup could be safely stored for a period of six months under both the ambient and refrigerated conditions without much change in various quality characteristics. However the changes in the quality characteristics of the syrup were slower in refrigerated storage conditions as compared to ambient conditions. Both the packaging materials viz., PET and glass bottles were found suitable, with comparatively less changes occurring in glass bottle under refrigerated conditions.